(untitled) (Psychology Travelogs, 2025)
The article analyzes the psychological characteristics of children’s emotional well-being in the context of prolonged separation from one of the parents due to military mobilization. The relevance of the study is determined by the growing number of children experiencing increased emotional vulnerability caused by disruptions in familiar family functioning. Emotional well-being is considered as a complex integrative construct that includes the ability to regulate emotions, a sense of security, emotional comfort, and support from significant adults. It is emphasized that the mobilization of a father or mother acts as a destabilizing factor in the child’s emotional environment. The theoretical analysis is based on leading psychological concepts – J. Bowlby’s attachment theory, E. Erikson’s psychosocial theory of development, and the cognitive-stress model of R. Lazarus and S. Folkman. The article shows that a child’s emotional response to separation significantly depends on age-specific features of psycho-emotional development. In particular, preschoolers predominantly experience separation anxiety and fear of loss; younger school-aged children exhibit emotional instability and adaptation difficulties; while adolescents may demonstrate aggression, ambivalence, or emotional detachment. Separation from parents during wartime disrupts the basic sense of trust in the world and creates preconditions for the development of emotional distress. This situation is further complicated by limited access to everyday social support, increasing the child’s vulnerability to prolonged psychological discomfort. Maintaining children’s emotional well-being effectively requires an interdisciplinary approach and coordinated efforts from psychological services, educational institutions, and families. The proposed theoretical generalizations may serve as a basis for developing strategies to overcome the negative consequences of emotional distress.